Element determination in hair by ICP-MS method : selection of a suitable sample washing procedure - Bošnjaković, Anja (Array, 2020)
Human hair is a biological sample that is, unlike blood, noninvasively collected and can be used in the assessment of element intake. Before analysis, hair samples need to be washed to eliminate external contamination, for which no standard procedure exists. The present study evaluated the efficiency of different processes for washing hair samples (by non-ionic detergent, acids, solvents, and their mixtures), including ultrasonication before ICP-MS element (As, Ca, Cd, Cu, Fe, Hg, Mg, Mn, Mo, Pb, Se, and Zn) analysis. All tested washing procedures using detergent or solvents were satisfactory, while nitric and hydrochloric acid solutions yielded to “released” and lost elements due to damaged hair (visible discolouration and hair impairment). The application of ultrasonication improved washing efficiency up to 10 %, depending on the tested element and washing procedure.